Interactive Multimedia Based on Mobile Device for Primary School Students - Hirnanda Dimas Pradana; Hirnanda Dimas Pradana (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
Since COVID-19 was declared a pandemic by the Indonesian government, the learning system has undergone adjustments. Learning from home with an online system is an alternative solution that can be applied. The research describes the results of developing interactive multimedia based on mobile devices. This development aims to provide a variety of learning media that can be collaborated with online methods. The research subjects were fourth-grade students, SDN 1 Babat Jerawat Surabaya. The development model used is an adaptation of Lee Owens. The development product was tested on media experts, material experts, and potential users. The trial aims to measure the validity of the media. The validation results from media experts obtained 88.24%, material expert validation obtained a score of 90.38%, and user trials obtained a score of 79.89%. Furthermore, the effectiveness of using media in learning is measured by conducting pre-tests and post-test on students. The percentage increase in the value obtained a score of 95%. Thus the interactive multimedia based on mobile devices developed has high effectiveness in improving student learning outcomes.